Rejuvenation of Recycled Asphalt Binders with Bio-Oils from Waste Biomass Pyrolysis - Yalcin, Beyza Furtana; Yilmaz, Mehmet; Yalcin, Erkut; Altundogan, Hamdi Soner (Asce-Amer Soc Civil Engineers, 2025)
This study evaluates the effects of using bio-oil obtained from waste biomass on the physical properties, rheology, fatigue, and rutting of recycled asphalt binder. In addition, the aim of this study is to provide benefits to the environment and the economy by reusing waste materials. The bio-oils produced were produced by the pyrolysis method. B70/100 pure bitumen was chosen as the reference binder for the rejuvenation of the selected RAP binder. To ensure its properties, five different rejuvenators (two commercial + three bio-based rejuvenators) were added to the aged bitumen obtained from recycled asphalt pavement (RAP) at different rates. The produced bio-oils were compared with commercial products. The first goal of the study is to produce rejuvenators from waste materials, and the second is to achieve similar or better results with commercial rejuvenators by producing rejuvenators from waste materials. When the test results are examined, it can be seen that the aged binder was rejuvenated to the desired hardness by adding rejuvenator to it. It is seen that the penetration value of the aged binder increased by the addition of rejuvenator, whereas the softening point and viscosity values decreased.
Keywords: Recycled asphalt pavements (RAP); Bio-oils; Waste biomass; Pyrolysis; Rejuvenating